2015
DOI: 10.32607/20758251-2015-7-1-87-97
|View full text |Cite
|
Sign up to set email alerts
|

The Role of HCV E2 Protein Glycosylation in Functioning of Virus Envelope Proteins in Insect and Mammalian Cells

Abstract: The hepatitis C virus (HCV) envelope proteins E1 and E2, being virion components, are involved in the formation of infectious particles in infected cells. The detailed structure of the infectious particle of HCV remains poorly understood. Moreover, the virion assembly and release of virions by the cell are the least understood processes. It is believed that virion properties depend on glycosylation of the virus envelope proteins in a cell, while glycansat several glycosylation sites of these proteins play a pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Moreover, the stalk mutation had similar effects in a closely related Nipah virus (Bradel-Tretheway et al 2015). In Hepatitis C Virus, disruption of specific N-glycosites in the two highly N-glycosylated envelope glycoproteins E1 and E2 results in formation of unproductive E1-E2 heterodimers (Meunier et al 1999;Goffard et al 2005;Orlova et al 2015), whereas specific O-glycosites on Hendra virus protein G have been shown to affect association with protein F (Stone et al 2016), suggesting both types of glycans can carry out similar functions. Similarly, Oglycosites have been found in regions of varicella zoster virus gE, important for interaction with partner gI ), but the glycan specific functions are yet to be uncovered.…”
Section: Roles Of Glycosylation On Viral Protein Complex Formationmentioning
confidence: 92%
See 2 more Smart Citations
“…Moreover, the stalk mutation had similar effects in a closely related Nipah virus (Bradel-Tretheway et al 2015). In Hepatitis C Virus, disruption of specific N-glycosites in the two highly N-glycosylated envelope glycoproteins E1 and E2 results in formation of unproductive E1-E2 heterodimers (Meunier et al 1999;Goffard et al 2005;Orlova et al 2015), whereas specific O-glycosites on Hendra virus protein G have been shown to affect association with protein F (Stone et al 2016), suggesting both types of glycans can carry out similar functions. Similarly, Oglycosites have been found in regions of varicella zoster virus gE, important for interaction with partner gI ), but the glycan specific functions are yet to be uncovered.…”
Section: Roles Of Glycosylation On Viral Protein Complex Formationmentioning
confidence: 92%
“…In addition to general functions, specific types of glycans on viral glycoproteins often affect receptor binding and cell fusion (Lin et al 2003;Lozach et al 2003;Gramberg et al 2005;Davis et al 2006;Miller et al 2008;Chen et al 2014;Phoenix et al 2016;Wang et al 2016). Moreover, it is becoming increasingly clear that distinct glycans play separate roles in various stages of the viral cycle (Goffard et al 2005;Falkowska et al 2007;Helle et al 2010;Wang et al 2013Wang et al , 2017Lennemann et al 2014;Bradel-Tretheway et al 2015;Luo et al 2015;Orlova et al 2015;Wu et al 2017). Some site-specific functions of viral glycosylation have been assigned for both N-and O-linked glycans mostly by site-directed mutagenesis studies.…”
Section: Roles Of Glycosylation In Virus Biologymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the competitive activity of such enzymes in space and time results in the creation of multiple proteoforms carrying an array of different structures and having variable numbers of occupied glycosites . This array of different viral glycan structures not only shields them from host immunity, but is often required for proper viral glycoprotein function . In addition, such a plethora of protein modifications, combined with mutagenesis due to selection pressure, may complicate the creation of potent and lasting vaccines.…”
Section: Site‐specific N‐ and O‐glycosylation In Enveloped Virusesmentioning
confidence: 99%
“…Analysis of O‐linked glycans on HCV E2 revealed considerable microheterogeneity at the six identified glycosites . Mutational analysis of specific N‐glycosites in the two envelope glycoproteins E1 and E2 has identified glycosites important for protein–protein interaction . Moreover, distinct putative N‐ and O‐glycosylation site mutations differentially affected viral particle production, infectivity, CD81 binding, and neutralizing antibody activity .…”
Section: Glycosylation Analysis Of Viral Glycoproteinsmentioning
confidence: 99%